Ultrafast laser welding method for ceramic reinforced aluminum matrix composite
Through ultrafast laser welding method, the problems of low welding strength and low accuracy of ceramic-reinforced aluminum-based composite materials are solved, and high-strength, high-precision welding and micro-zone welding are achieved. It is suitable for multi-position welding and is easy to operate in atmospheric environments.
Patent Information
- Application Number
- CN202511049967.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-09-05
AI Technical Summary
The existing ceramic reinforced aluminum-based composite welding methods have problems such as low joint connection strength, low welding accuracy and high welding environment requirements, making it difficult to achieve high-strength, high-precision welding and micro-zone welding.
The ultrafast laser welding method is adopted, and the surface of the welded part is processed through mechanical grinding and polishing, and the ultrafast laser is used for welding. The laser pulse width is controlled to be 20fs~10ps, the laser power is 1~100W, the welding speed is 0.01~3mm/s, and the defocus amount is -150~0μm, achieving high-precision welding of ceramic-reinforced aluminum-based composite materials.
It has achieved the improvement of joint strength, high density of welds, small deformation of welding, high precision and micro-zone welding, and is carried out in an atmospheric environment, simple operation, and suitable for multi-position welding.
Smart Images

Figure CN120587675A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal matrix composite material connection, and in particular relates to an ultrafast laser welding method for ceramic reinforced aluminum matrix composite materials. Background Art
[0002] Metal-matrix composites (MMCs) are composite materials made from a metal matrix such as Al, Ti, Cu, and Mg, reinforced with inorganic non-metallic materials such as ceramics, boron, and graphite. Compared to metals, MMCs offer higher strength, hardness, wear resistance, and superior high-temperature performance, holding great promise for applications in aerospace, automotive, electronics, and medicine. Ceramic-reinforced aluminum-matrix composites (CMCs) significantly improve their specific strength, specific stiffness, wear resistance, corrosion resistance, thermal stability, and fatigue performance compared to their matrix alloys. In the aerospace sector, replacing titanium alloys with CMCs significantly reduces component weight, improves thermal conductivity, and reduces costs. ACMs are also used in heat sinks for electronic devices. By adjusting the reinforcing phase content in the composite, the thermal expansion coefficient can be matched to the device, reducing packaging failures caused by thermal stress. However, CMCs are difficult to machine, and single-piece molded components struggle to meet complex structural requirements. Consequently, welding is required to join simple parts together to create complex components, and component repairs also require welding. Therefore, the development of welding technology for CMCs is crucial for engineering applications.
[0003] Since aluminum itself is very active in chemical properties, it is very easy to react with the reinforcement phase to form brittle compounds under the high temperature conditions of fusion welding. Brittle compounds of large size or large area will have an adverse effect on the joint performance. In 2000, A. Ureña team (A.Ureña, MDEscalera, L.Gil. Influence of interface reactions on fracturemechanisms in TIG arc-welded aluminium matrix composites [J]. CompositesScience and Technology, 2000, 60(4): 613-22.) conducted TIG welding on aluminum matrix composites reinforced with different volume fractions of SiC. The study found that with the increase of SiC volume fraction, the degradation of joint performance became more and more serious. 20vol%SiC pThe tensile strength of a 1.5-1.5 mm / s / Al (1.5-1.5 mm / s) joint achieved under the optimal welding process parameters (current 50A, voltage 16.4V, power 820W) is only 137 MPa, less than 45% of the parent material strength. This is primarily due to the reaction between SiC and the aluminum matrix under the high arc temperature, forming the brittle Al4C3 phase. The higher the SiC volume fraction in the parent material, the more likely Al4C3 is to form, resulting in more defects in the joint. Furthermore, the generated Al4C3 is highly susceptible to hydrolysis, which can easily cause corrosion. Zhang Jianxun et al. have disclosed a method for homogenizing the reinforcement phase in aluminum-based composites using an inserted ultrasonic vibration-assisted laser welding method (Patent No.: CN202411647026.5). Using conventional laser welding methods, a variable-amplitude tungsten needle is inserted into the molten pool to impart vibration to the weld pool, resulting in a highly uniform distribution of the reinforcement phase in the joint. This method enables the welding of aluminum-based composites reinforced with silicon carbide particles (volume fraction 5-25%). However, it should be noted that welding aluminum-based composites reinforced with high volume fractions of SiC using this method can cause severe wear on the tungsten needle. Furthermore, SiC easily reacts with Al to form the brittle Al4C3 phase, making this method unsuitable for welding aluminum-based composites reinforced with high volume fractions of SiC. Lin Tiesong et al. (Patent No. ZL201110179638.2) disclose a welding method for aluminum-based composites reinforced with high volume fractions of ceramic. The method first sputter-deposits an active Ti layer with a thickness of 500 nm to 2 μm on the surface of the ceramic-reinforced aluminum-based composite, followed by vacuum brazing using an Al-Si-Mg filler metal. The Ti layer improves the wettability of the filler metal with the parent metal, resulting in a joint with good interfacial bonding and no obvious defects. However, it should be noted that the welding accuracy of this method is significantly affected by the sputter-deposited active layer area and thickness, as well as the filler metal loading. This makes it difficult to precisely control the thickness, area, and filler metal loading of the intermediate layer to achieve high-precision welding and micro-area welding. In addition, Niu Jitai et al. (Niu Jitai, Wang Muzhen, Liu Liming, Kong Lingchao. Behavior of oxide film in Al2O3p / 6061Al composites under diffusion welding conditions [J]. Journal of Materials Research, 2000, (03): 244-8.) reported the diffusion welding of Al2O3 reinforced aluminum matrix composites with a volume fraction of 30%. It was found that the oxide film on the surface of the composite material would hinder the atomic diffusion during the welding process. When the joining temperature exceeded the solidus temperature of the aluminum matrix composite matrix, liquid metal would appear on the contact surface, and this phenomenon could be alleviated. It was found that the composite material was connected under the conditions of vacuum degree 0.133Pa, welding temperature 620℃, and joining pressure 5MPa. Under these parameters, the oxide film of the joint obtained was refined, the content was reduced, and the tensile strength was increased to 165MPa. However, this method must apply pressure to the workpiece during the welding process, causing plastic deformation of the matrix. Therefore, this method is difficult to achieve high-precision welding and micro-area welding.
[0004] In summary, the currently reported welding methods for ceramic-reinforced aluminum-based composite materials have the following disadvantages: 1. Low joint strength: The large amount of brittle compounds generated by the reaction between the aluminum alloy matrix and the ceramic reinforcement phase seriously damages the interfacial bonding between the matrix and the reinforcement phase, becoming a source of cracks in the joint and adversely affecting the joint strength. This phenomenon is particularly serious for aluminum-based composite materials reinforced with high volume fractions of ceramic. 2. Low welding precision: Traditional melting welding methods require a large heat input to the joint, resulting in a large weld width and heat-affected zone, and large joint deformation; the precision of the brazed joint is greatly affected by the thickness, area, and amount of brazing filler metal; solid-phase welding is limited by the method itself and can cause material deformation. Existing welding technologies are unable to achieve high-precision welding or micro-area welding of materials. 3. High welding conditions: Aluminum alloys are active and easily oxidized under high-temperature air conditions. Traditional welding methods such as laser, arc welding, and brazing all require special environments such as high-purity Ar gas protection or vacuum. Therefore, it is urgent to develop a new connection method that can achieve high-strength, low-deformation high-precision welding and micro-area welding directly under atmospheric conditions. Summary of the Invention
[0005] In order to solve the problems of low strength, difficulty in achieving high-precision welding and micro-area welding, and high welding environment requirements in existing ceramic reinforced aluminum-based composite material connection methods, the present invention provides an ultrafast laser welding method for ceramic reinforced aluminum-based composite materials.
[0006] The ultrafast laser welding method of the ceramic reinforced aluminum matrix composite material of the present invention is implemented by the following steps:
[0007] 1. Mechanically grinding and polishing the surfaces to be joined of the ceramic reinforced aluminum matrix composite material to be welded, and then ultrasonically cleaning them to obtain the composite material to be welded;
[0008] 2. Using a fixture, assemble the composite materials to be welded in a butt-jointed manner to obtain an assembly to be welded;
[0009] 3. Use ultrafast laser to align the weld seam of the assembly to be welded, control the laser pulse width to 20fs~10ps, the laser power to 1~100W, the welding speed to 0.01~3mm / s, and the defocus to -150~0μm to perform ultrafast laser welding, thereby completing the ultrafast laser welding of ceramic reinforced aluminum-based composite materials.
[0010] Compared with the existing ceramic reinforced aluminum matrix composite material welding technology, the ultrafast laser welding method of the ceramic reinforced aluminum matrix composite material of the present invention has the following advantages:
[0011] 1. High joint strength: Due to the extremely short pulse width of the ultrafast laser, the thermal impact and thermal damage to the ceramic-reinforced aluminum-based composite material are minimal. The material cools very quickly during welding, the molten pool exists for a short time, and the high-temperature liquid aluminum matrix and the reinforcement phase are in contact for a short time. Therefore, the reaction between the aluminum matrix and the reinforcement phase to form brittle compounds can be effectively suppressed. The weld obtained by the melting and resolidification process of the material at the weld is denser than the parent material, without defects such as lack of fusion and porosity, and the joint strength is improved.
[0012] 2. High-precision welding and micro-area welding can be achieved: The weld size obtained by ultrafast laser welding is at the micron level, and there is almost no heat-affected zone. The welding deformation is extremely small, and directional welding can be performed on micron-level areas, which can well achieve high-precision welding and micro-area welding.
[0013] 3. Simple operation: This method can achieve highly automated welding. After simple assembly and setting of welding parameters, no manual operation is required and the welding process can be completed by relying on the movement of a robotic arm or platform.
[0014] 4. Broad application prospects: Ceramic-reinforced aluminum-based composite materials have excellent performance and are suitable for a variety of scenarios. This welding method can be directly welded in an atmospheric environment, and the welding conditions are relatively low.
[0015] 5. Multi-position welding can be achieved: The path setting can be used to make the laser move in a specific direction relative to the workpiece to be welded, thus achieving multi-position welding. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a secondary electron photograph of a 0.5 mm thick 45 vol% SiC reinforced aluminum matrix composite butt weld obtained in Example 1 using a laser with a wavelength of 1030 nm, a frequency of 1 MHz, a pulse width of 300 fs, a laser power of 19.78 W, and a welding speed of 0.05 mm / s;
[0017] Figure 2 This is a backscattered electron photograph of a 0.5 mm thick 45 vol% SiC reinforced aluminum matrix composite butt weld obtained in Example 1 using a laser with a wavelength of 1030 nm, a frequency of 1 MHz, a pulse width of 300 fs, a laser power of 19.78 W, and a welding speed of 0.05 mm / s;
[0018] Figure 3 This is a secondary electron photograph of a four-point bending fracture of a 0.5 mm thick 45 vol% SiC reinforced aluminum matrix composite butt weld obtained in Example 1 using a laser with a wavelength of 1030 nm, a frequency of 1 MHz, a pulse width of 300 fs, a laser power of 19.78 W, and a welding speed of 0.05 mm / s;
[0019] Figure 4This is the X-ray diffraction spectrum of the 0.5 mm thick 45 vol% SiC reinforced aluminum matrix composite weld obtained in Example 1 using a laser with a wavelength of 1030 nm, a frequency of 1 MHz, a pulse width of 300 fs, a laser power of 19.78 W, and a welding speed of 0.05 mm / s.
[0020] Figure 5 This is a backscattered electron photograph of a 0.5 mm thick 45 vol% SiC reinforced aluminum matrix composite butt weld obtained in Example 2 using a laser with a wavelength of 1030 nm, a frequency of 1 MHz, a pulse width of 300 fs, a laser power of 21.62 W, and a welding speed of 0.05 mm / s. DETAILED DESCRIPTION
[0021] Specific embodiment 1: The ultrafast laser welding method of ceramic reinforced aluminum matrix composite material in this embodiment is implemented according to the following steps:
[0022] 1. Mechanically grinding and polishing the surfaces to be joined of the ceramic reinforced aluminum matrix composite material to be welded, and then ultrasonically cleaning them to obtain the composite material to be welded;
[0023] 2. Using a fixture, assemble the composite materials to be welded in a butt-jointed manner to obtain an assembly to be welded;
[0024] 3. Use ultrafast laser to align the weld seam of the assembly to be welded, control the laser pulse width to 20fs~10ps, the laser power to 1~100W, the welding speed to 0.01~3mm / s, and the defocus to -150~0μm to perform ultrafast laser welding, thereby completing the ultrafast laser welding of ceramic reinforced aluminum-based composite materials.
[0025] The thickness of the ceramic reinforced aluminum matrix composite material in step 1 of this embodiment is 0.2-3 mm. In step 2, the assembly of the composite material to be welded may be performed without pressurization.
[0026] In this embodiment, laser power and welding speed are two key factors affecting welding quality. Together, they determine the amount of heat input to the material during welding. Excessive or insufficient heat input will not result in high-quality welding. When the laser power is too low or the welding speed is too high, the heat input to the material is low, making it difficult to achieve full penetration of the workpiece. When the laser power is too high or the welding speed is too low, the heat input to the material is excessive, potentially causing severe weld oxidation or significant deformation of the joint, adversely affecting joint performance.
[0027] The ultrafast laser welding method of this embodiment can effectively inhibit the reaction between the aluminum matrix and the reinforcement phase to form brittle compounds, obtain a weld with higher density, significantly improve the joint strength, and achieve welding and micro-area welding with micron-level and lower precision.
[0028] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the ceramic reinforcement phase in the ceramic reinforced aluminum-based composite material is SiC, Al2O3, B4C, TiC or TiB2, and the volume fraction of the ceramic reinforcement phase is 10% to 70%.
[0029] This embodiment is applicable to welding of ceramic-reinforced aluminum-based composite materials with a high reinforcing phase content (40 vol % or more).
[0030] Specific embodiment three: This embodiment differs from specific embodiment one or two in that the mechanical polishing in step one is to polish the surface to be connected with 400#, 800#, 1500#, 2000# and 3000# SiC sandpaper in sequence.
[0031] Specific embodiment 4: The difference between this embodiment and any one of specific embodiments 1 to 3 is that the polishing in step 1 is performed using a 0.05 μm SiO 2 suspension.
[0032] Specific embodiment 5: The difference between this embodiment and specific embodiments 1 to 4 is that in step 1, ultrasonic cleaning is performed using soapy water, deionized water and anhydrous ethanol in sequence, and each ultrasonic cleaning lasts 3 to 10 minutes.
[0033] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the assembly pitch at the welding starting point in step 2 is less than 5 μm, and the assembly pitch at the welding end point is 5-50 μm.
[0034] Specific embodiment seven: This embodiment differs from any one of specific embodiments one to six in that the pulse width of the ultrafast laser in step three is 200 fs to 2 ps.
[0035] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that the wavelength range of the ultrafast laser in step three is 800-1030 nm, and the laser frequency is 0.5-1.5 MHz.
[0036] Specific embodiment nine: The difference between this embodiment and any one of specific embodiments one to eight is that in step three, the laser power is controlled to be 10~30W, the welding speed is 0.02~1mm / s, the defocus amount is -150~0μm, the welding passes are 1~5 times, and ultrafast laser welding is performed.
[0037] Specific embodiment ten: This embodiment differs from any one of specific embodiments one to nine in that the welding path in step three is linear, zigzag, sinusoidal or circular.
[0038] Example 1: The ultrafast laser welding method of ceramic reinforced aluminum matrix composite material of this embodiment is implemented according to the following steps:
[0039] First, a 45 vol% SiC reinforced aluminum matrix composite material was processed into two 0.5 mm thick parts to be welded. The surfaces to be joined were polished with 400#, 800#, 1500#, 2000#, and 3000# SiC sandpaper in sequence. After polishing, they were polished with a 0.05 μm SiO2 suspension. Then, they were ultrasonically cleaned in soapy water, deionized water, and anhydrous ethanol for 5 min each to obtain the composite material to be welded.
[0040] 2. Use a fixture to assemble the composite materials to be welded in a butt-jointed manner, with the assembly spacing at the welding start point being less than 5 μm and the assembly spacing at the welding end point being 30 μm, to obtain the assembly to be welded;
[0041] 3. Use ultrafast laser to align the weld of the assembly to be welded. The laser wavelength is 1030nm, the pulse width is 300fs, the laser frequency is 1MHz, the welding power is controlled to 19.78W, the welding speed is 0.05mm / s, the defocus is 0μm, the welding is done once, and the welding path is linear, thereby completing the ultrafast laser welding of ceramic reinforced aluminum-based composite materials.
[0042] A four-point bending strength test was performed on the 45 vol% SiC reinforced aluminum-based composite material joint obtained in this embodiment. The average bending strength was approximately 311 MPa when the weld was subjected to compressive stress on the side close to the light source, and the average bending strength was approximately 284 MPa when the weld was subjected to tensile stress on the side close to the light source. The method of this embodiment can achieve high-quality SiC reinforced aluminum-based composite material connection.
[0043] The low-magnification secondary electron photograph and high-magnification backscattered electron photograph of the cross section of the 45 vol% SiC reinforced aluminum matrix composite butt joint obtained in this embodiment under the conditions of laser power 19.78 W and welding speed 0.05 mm / s are shown in Figures 2 and 3, respectively. Figure 1 and Figure 2 As shown, the secondary electron photo of the four-point bending fracture morphology of the joint is as follows Figure 3 As shown, the X-ray diffraction spectrum of the weld is as follows Figure 4 shown.
[0044] from Figure 1 、 Figure 2 and Figure 3 It can be seen that the joint obtained by the method of this embodiment has a much higher density than the parent material after the melting and solidification process, and has no defects such as unfused, pores, and hydrolysis pits, and the joint connection quality is high. The weld is formed with excess height, the weld width is about 60μm, and the welding deformation is extremely small, which can well achieve high-precision welding and micro-area welding. Figure 4The X-ray diffraction spectrum at the weld and the PDF card information corresponding to the diffraction peaks show that the weld can be roughly divided into two regions. The top of the weld near the light source undergoes oxidation in the atmosphere and is Al2O3. The remaining portion is mainly composed of Al and SiC, with a small amount of Al-Mg or Al-Cu compounds. There is no Al4C3 diffraction peak, indicating that no Al4C3 is generated in the weld. This is mainly because this method has little thermal impact and thermal damage to the material. The material cools very quickly during welding, the molten pool exists for a short time, and the high-temperature liquid aluminum matrix is in contact with the SiC reinforcement phase for a short time. Therefore, it can effectively inhibit the reaction between the aluminum matrix and SiC to form the Al4C3 brittle phase, thereby obtaining a higher joint strength.
[0045] Example 2: The ultrafast laser welding method of ceramic reinforced aluminum matrix composite material of this embodiment is implemented according to the following steps:
[0046] First, a 45 vol% SiC reinforced aluminum matrix composite material was processed into two 0.5 mm thick parts to be welded. The surfaces to be joined were polished with 400#, 800#, 1500#, 2000#, and 3000# SiC sandpaper in sequence. After polishing, they were polished with a 0.05 μm SiO2 suspension. Then, they were ultrasonically cleaned in soapy water, deionized water, and anhydrous ethanol for 5 min each to obtain the composite material to be welded.
[0047] 2. Use a fixture to assemble the composite materials to be welded in a butt-jointed manner, with the assembly spacing at the welding start point being less than 5 μm and the assembly spacing at the welding end point being 30 μm, to obtain the assembly to be welded;
[0048] 3. Use ultrafast laser to align the weld of the assembly to be welded. The laser wavelength is 1030nm, the pulse width is 300fs, the laser frequency is 1MHz, the welding power is controlled to 21.62W, the welding speed is 0.05mm / s, the defocus is 0μm, the welding is done once, and the welding path is linear, thereby completing the ultrafast laser welding of ceramic reinforced aluminum-based composite materials.
[0049] A four-point bending strength test was performed on the 45 vol% SiC reinforced aluminum-based composite material joint obtained in this embodiment. The average bending strength was approximately 345 MPa when the weld was subjected to compressive stress on the side close to the light source, and the average bending strength was approximately 262 MPa when the weld was subjected to tensile stress on the side close to the light source. The method of this embodiment can achieve high-quality SiC reinforced aluminum-based composite material connection.
[0050] The high-magnification backscattered electron photograph of the cross section of the 45 vol% SiC reinforced aluminum matrix composite butt joint obtained in this embodiment under the conditions of laser power 21.62 W and welding speed 0.05 mm / s is as follows: Figure 5As shown, it can be seen that the joint obtained by using the method of this embodiment is relatively dense, without defects such as unfused joints, pores, and hydrolysis pits, and the joint connection quality is high.
Claims
1. An ultrafast laser welding method for ceramic reinforced aluminum matrix composites, characterized in that The ultrafast laser welding method is implemented according to the following steps:
1. Mechanically grinding and polishing the surfaces to be joined of the ceramic reinforced aluminum matrix composite material to be welded, and then ultrasonically cleaning them to obtain the composite material to be welded; 2. Using a fixture, assemble the composite materials to be welded in a butt-jointed manner to obtain an assembly to be welded; 3. Use ultrafast laser to align the weld seam of the assembly to be welded, control the laser pulse width to 20fs~10ps, the laser power to 1~100W, the welding speed to 0.01~3mm / s, and the defocus to -150~0μm to perform ultrafast laser welding, thereby completing the ultrafast laser welding of ceramic reinforced aluminum-based composite materials.
2. The ultrafast laser welding method for ceramic reinforced aluminum matrix composites according to claim 1, characterized in that The ceramic reinforcement phase in the ceramic reinforced aluminum-based composite material is SiC, Al2O3, B4C, TiC or TiB2, and the volume fraction of the ceramic reinforcement phase is 10% to 70%.
3. The ultrafast laser welding method for ceramic reinforced aluminum matrix composites according to claim 1, characterized in that In step 1, mechanical grinding is to grind the surface to be connected with 400#, 800#, 1500#, 2000# and 3000# SiC sandpaper in sequence.
4. The ultrafast laser welding method for ceramic reinforced aluminum matrix composites according to claim 1, characterized in that In step 1, polishing is performed using a 0.05 μm SiO2 suspension.
5. The ultrafast laser welding method for ceramic reinforced aluminum matrix composites according to claim 1, characterized in that In step 1, ultrasonic cleaning is performed using soapy water, deionized water, and anhydrous ethanol in sequence, with each ultrasonic cleaning lasting 3 to 10 minutes.
6. The ultrafast laser welding method for ceramic reinforced aluminum matrix composites according to claim 1, characterized in that The assembly spacing at the welding starting point of the assembly in step 2 is less than 5 μm, and the assembly spacing at the welding end point is 5~50 μm.
7. The ultrafast laser welding method for ceramic reinforced aluminum matrix composites according to claim 1, characterized in that The ultrafast laser pulse width in step 3 is 200fs~2ps.
8. The ultrafast laser welding method for ceramic reinforced aluminum matrix composite materials according to claim 1, characterized in that The wavelength range of the ultrafast laser in step 3 is 800~1030nm, and the laser frequency is 0.5~1.5MHz.
9. The ultrafast laser welding method for ceramic reinforced aluminum matrix composite materials according to claim 1, characterized in that In step 3, the laser power is controlled to be 10-30 W, the welding speed is 0.02-1 mm / s, the defocus amount is -150-0 μm, and the welding pass is 1-5 times to perform ultrafast laser welding.
10. The ultrafast laser welding method of ceramic reinforced aluminum matrix composite material according to claim 1, characterized in that In step 3, the welding path is linear, zigzag, sinusoidal or circular.
Citation Information
Patent Citations
Welding method of high-volume-content ceramic reinforced Al-base composite material
CN102350553A
Method for homogenizing reinforced phase of inserted ultrasonic vibration-assisted laser welding aluminum-based composite material
CN119282403A
Cited By
Method for ultrafast laser welding of ceramic reinforced aluminum-based composite material in vacuum environment
CN121732985A